ความเชื่อเหนือธรรมชาติที่ปรากฏในสำนวนไทย - เดชบำรุง, สมใจ; ชัยญาณะ, สิริวันทน์ (วารสาร ศึกษาศาสตร์ มมร; Vol 4 No 2 (2016): วารสารศึกษาศาสตร์ มมร ปีที่ 4 ฉบับที่ 2 (กรกฎาคม-ธันวาคม 2559), 2017)
งานวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสำนวนไทยซึ่งมีที่มาจากความเชื่อในสิ่งเหนือธรรมชาติ 2) วิเคราะห์ความหมายของสำนวนไทยที่เกี่ยวข้องกับความเชื่อเหนือธรรมชาติ โดยศึกษาและวิเคราะห์สำนวนไทยในหนังสือสำนวนไทย 5 เล่ม   ผลการวิจัยพบว่า สำนวนไทยที่เกี่ยวข้องกับความเชื่อเหนือธรรมชาติรวมทั้งสิ้น 133 สำนวน และที่มาของสำนวนไทยอันเกิดจากความเชื่อเหนือธรรมชาติ 8 ประเภท ซึ่งพบความเชื่อด้านสิ่งศักดิ์สิทธิ์ในสำนวนไทยมากที่สุด รองลงมาคือเรื่องภูตผีวิญญาณ และนรกสวรรค์ Abstract  The objectives of this study were: (1) To examine Thai idioms which originated from the belief in the supernatural beings. (2) To analyze the meanings of Thai idioms which originated from the belief in the supernatural beings, research using descriptive analysis of Thai idioms found in 5 collections of Thai idioms as the objects of the study. The results findings as follows:  There were 133 Thai idioms, categorized into 8 categories, which found as originating from the belief in supernatural beings. The most frequently found category of the belief in supernatural beings was the sacred beings, followed in order by the human spirits, wraith, heaven and the hell.